State of the union: glycobiology and immunology in the Canadian Rockies - Cobb, Brian (2011)
This March nearly 150 investigators attended the first international meeting focused solely on the role of glycans within the immune system. This Keystone Symposia meeting entitled “New Frontiers at the Interface of Immunity and Glycobiology” took place at Lake Louise, Alberta, Canada and was organized by Brian Cobb, Gabriel Rabinovich, and Yvette van Kooyk. We are pleased to report that the state of this union is strong and growing. “Glycoimmunology” includes both the immunology and glycobiology communities and is a rapidly expanding field as the involvement of carbohydrates in host responses rises to prominence. This growing awareness is visible within the Consortium for Functional Glycomics, led by the meeting's keynote speaker Jim Paulson of the Scripps Research Institute in La Jolla, CA, in which more than half of the 540 participating investigators have a stated interest in understanding the role of glycans and glycan-binding proteins within the immune system. Although the society-oriented meetings for glycobiology and immunology do touch on some of the areas of convergence, it is clear that they do not adequately cover the diverse areas of active investigation at this interface. As a result, the two underlying goals of this meeting were to bring those investigators together to better define the glycoimmunology field and to raise awareness of the importance of glycans in the immune system.